2001
DOI: 10.1093/ndt/16.suppl_4.12
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic methods to detect β2‐microglobulin associated amyloidosis (Aβ2‐microglobulin amyloidosis)

Abstract: beta2-Microglobulin-derived amyloidosis (Abeta2m) represents a major cause or morbidity in patients with end-stage renal disease. Symptoms of Abeta2m amyloid are mainly related to (peri-) articular amyloid deposition. Conventional non-invasive diagnostic techniques, i.e. clinical evaluation, joint ultrasonography or X-ray, computed tomography or magnetic resonance imaging findings, as well as conventional bone scans, suffer from relative non-specificity and/or low sensitivity. Two recent methods, namely scinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Both substances show a specific enrichment in amyloid tissue and have been proven to be more sensitive than other noninvasive techniques in the diagnosis of Ab 2 M amyloidosis, even in asymptomatic patients, and can be used for monitoring disease progress (46,47,49,50). The most advanced step in imaging amyloidosis in dialysis patients is the use of 111 In-labeled recombinant human b 2 M (rhb 2 M), which allows the sensitive and specific noninvasive detection of b 2 M amyloidosis with a relatively low radioactive burden and good image quality (46,47). If direct scintigraphic imaging of Ab 2 M amyloidosis becomes more widely available, it could be used as an efficient tracer in monitoring therapeutic regimens in dialysis patients with amyloidosis.…”
Section: Ab 2 M Amyloidosismentioning
confidence: 99%
See 2 more Smart Citations
“…Both substances show a specific enrichment in amyloid tissue and have been proven to be more sensitive than other noninvasive techniques in the diagnosis of Ab 2 M amyloidosis, even in asymptomatic patients, and can be used for monitoring disease progress (46,47,49,50). The most advanced step in imaging amyloidosis in dialysis patients is the use of 111 In-labeled recombinant human b 2 M (rhb 2 M), which allows the sensitive and specific noninvasive detection of b 2 M amyloidosis with a relatively low radioactive burden and good image quality (46,47). If direct scintigraphic imaging of Ab 2 M amyloidosis becomes more widely available, it could be used as an efficient tracer in monitoring therapeutic regimens in dialysis patients with amyloidosis.…”
Section: Ab 2 M Amyloidosismentioning
confidence: 99%
“…The “gold standard” for diagnosis is considered to be histologic confirmation of β 2 M amyloid; however, biopsy is seldom performed. The radionuclide bone scan in Aβ 2 M amyloidosis is neither specific nor very sensitive (47). Imaging with gallium 67 citrate or Tl‐201 chloride has been reported to be accurate in evaluating the activity and response to therapy of such lesions (48).…”
Section: Aβ2m Amyloidosismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that scintigraphy in which the radioactive tracer (iodine 131 or indium 111) is labeled to the amyloid precursor protein ␤ 2 -microglobulin is superior to MRI in demonstrating deposition of ␤ 2 -microglobulin amyloid in dialysis patients. 13,14 This is particularly so when recombinant human ␤ 2 -microglobulin is used as the labeling agent. 14…”
Section: Discussionmentioning
confidence: 99%
“…The radiotracer is accumulated directly in amyloid deposits [32]. A disadvantage of 131 I-labeled radiotracer was poor spatial resolution, which made imaging of small joints problematic and increased the radiation dose due to unnecessary β(−) radiation [34]. In 2000, Schaeffer combined β2M with gamma emitter 111 In [35].…”
Section: Radiotracers Used For Imaging Of Amyloid Depositsmentioning
confidence: 99%